Drug allergy evaluation in children with suspected mild antibiotic allergy - Kitsos, Nikolaos; Cassimos, Dimitrios; Trypsianis, Grigorios; Xinias, Ioannis; Roilides, Emmanouil; Grivea, Ioanna; Mantadakis, Elpis; Mavroudi, Antigoni (Frontiers in Allergy, 2022)
Background Adverse antibiotic reactions caused by an immunological mechanism are known as allergic reactions. The percentage of reported antibiotic allergies is likely to differ from the one validated after a drug provocation test (DPT) with the culprit antibiotic. This study aimed to compare the percentage of children who were thought to be allergic to a certain antibiotic with those who have a true allergy, as confirmed by DPTs. We also validated Skin Prick Tests (SPTs) and Intradermal Tests (IDTs) by assessing their sensitivity and specificity, in diagnosing antibiotic allergies using DPT as the gold standard. Furthermore, we investigated epidemiological risk factors such as personal and family history of atopic disease and eosinophilia. Methods Children with a history of possible allergic reaction to an antibiotic underwent a diagnostic procedure that included: 1) Eosinophil blood count, 2) SPTs, 3) IDTs and 4) DPTs. The parameters were compared with Pearson’s Chi-Square and Fisher’s Exact Test. Several risk factors that were found significant in univariate analysis, were examined with multiple logistic regression analysis to see if they were related to a higher risk for a positive DPT. Results Semi-synthetic penicillin was the most common group of antibiotics thought to cause allergic reactions in this study. Overall, 123 children with a personal history of an adverse reaction to a certain antibiotic, were evaluated. In 87.8% of the cases, the symptoms had occurred several hours after administration of the culprit antibiotic. Both SPTs and IDTs had low sensitivity but high specificity. Moreover, they had a high positive predictive value (PPV). In contrast, eosinophilia was not recognized as a risk factor. Seventeen patients (13.8%) had a true antibiotic allergy, as confirmed by a positive DPT. A positive IDT was a strong predictor of a positive DPT, along with a positive personal and family history of atopy. Conclusion SPTs and IDTs are very reliable in confirming antibiotic allergy when found positive. A negative result of a SPT highly predicts a negative DPT. A positive IDT and a positive personal and family history of atopy were recognized as significant risk factors for antibiotic allergy.